1999
DOI: 10.1002/(sici)1522-2683(19990701)20:9<1890::aid-elps1890>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Study of interaction between drug enantiomers and serum albumin by capillary electrophoresis

Abstract: The interaction between drugs and human serum albumin (HSA) was investigated by capillary electrophoresis (CE). It involves stereoselectivity, drug displacement and synergism effects. Under protein‐drug binding equilibrium, the unbound concentrations of drug enantiomers were measured by frontal analysis (FA). The stereoselectivity of verapamil (VER) binding to HSA was proved by the different free fractions of two enantiomers. In physiological pH (7.4, ionic strength 0.17 phosphate buffer) when 300 μM (±) VER w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 16 publications
2
27
0
Order By: Relevance
“…Salicylic acid was added to the samples to displace bilirubin from HSA, thus, overcoming the sensitivity problems. The versatility of CE-FA for probing of binding sites on HSA by displacement studies has also been demonstrated elsewhere [34,74].…”
Section: Human Serum Albumin Bindingmentioning
confidence: 77%
See 3 more Smart Citations
“…Salicylic acid was added to the samples to displace bilirubin from HSA, thus, overcoming the sensitivity problems. The versatility of CE-FA for probing of binding sites on HSA by displacement studies has also been demonstrated elsewhere [34,74].…”
Section: Human Serum Albumin Bindingmentioning
confidence: 77%
“…The utility and validity of binding studies performed with CE-FA have been demonstrated in several studies using HSA and various cationic ligands such as propranolol and verapamil [36,42,[71][72][73][74]. CE-FA is ideally suited for the measurement of these interactions because the electrophoretic mobilities of the cationic ligands and HSA (negatively charged at physiological pH) are very different; moreover, the interactions between HSA and cationic drugs in general are relatively weak [65,66].…”
Section: Human Serum Albumin Bindingmentioning
confidence: 99%
See 2 more Smart Citations
“…Not only the chiral recognition of drug enantiomers by HSA but also the competitive binding of drug enantiomers to HSA can be studied. When ibuprofen was added to a verapamil-HSA sample, R-verapamil was partially displaced but S-verapamil not at all [99]. FA was applied to investigate the role of glycan structures in the enantioselective binding of basic drugs to a-acid glycoprotein (a-AGP).…”
Section: Protein-small Molecule Interactionmentioning
confidence: 99%